Efektivitas Sanksi Pengebirian Dalam Undang-Undang Perlindungan Anak Terhadap Predator Seksual Di Indonesia - Meliana Damayanti (LPPM Universitas Harapan Bangsa, 2019)
The focus of this paper is in area criminal law especially about the effectiveness of sanctions in the Child Protection Act against sexual predators in Indonesia related to additional punishment in the form of castration. This kind of punishment is the answer of the President of Republic Indonesia, Joko Widodo, to cope with the cruel sexual harassment to children. The crime rate showed a marked increase day by day. Furthermore, the motive of the sexual predators is become widespread and occurs in almost all regions in Indonesia. The castration issue of sanctions is a controversial issue. Many people concur with this kind of sanction. Meanwhile, others dis-agree on it because of some reasons. The purpose of this article is to review the formulation of a new sanction in Indonesia is regulated by Government Regulation of Lieu of Law (Perppu) No. 1 /2016 as the second amendment to the Child Protection Act that already issues as an Act. This article uses normative studies, including reviewing or analyzing primary and secondary data in the form of legal materials to understand the law as a set of rules or positive norms in the legislation system that regulates the human life which are the relevant regulations as well as the concept of punishment the principle of fairness. Hence, this article can be understood as a literature study. The objective of this article is considerable contribution for the policy maker to evaluate the new existing legislation and to suggest possibilities of law reform. Keywords: Children, Sanction, Child Protection, Sexual Predators, Indonesia.